2016
DOI: 10.1007/s00246-016-1495-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Associations of Early Dysnatremias in Critically Ill Neonates and Infants Undergoing Cardiac Surgery

Abstract: subjects that demonstrated DN before surgery. Serum sodium levels were recorded for the first 72 h post-operatively. DN was present in 54% of the subjects (98/183): hypernatremia in 60 (33%), hyponatremia in 38 (21%). Multivariate analysis revealed that mild hypernatremia (146-150 mmol/dl) and moderate hypernatremia (151-155 mmol/dl) were associated with longer hospital length of stay (LOS, p < 0.05) and ventilation times (p < 0.05). No association was shown between mild/moderate hyponatremia (125-134 mmol/dl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 13 publications
3
19
2
2
Order By: Relevance
“…Fluctuations in sodium concentrations have been described in several studies, including children and adults admitted to intensive care, 5,14 although with variable outcomes. Previous studies have demonstrated prolonged LOS in association with hypernatremia, 9,10 whereas others have demonstrated more complications and prolonged LOS in association with hyponatremia 5,15 . The reason for these discrepancies may relate to time points for blood sampling and patient populations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Fluctuations in sodium concentrations have been described in several studies, including children and adults admitted to intensive care, 5,14 although with variable outcomes. Previous studies have demonstrated prolonged LOS in association with hypernatremia, 9,10 whereas others have demonstrated more complications and prolonged LOS in association with hyponatremia 5,15 . The reason for these discrepancies may relate to time points for blood sampling and patient populations.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have focused on outcomes in relation to sodium disturbances in critically ill patients, 5,14,15 including postcardiac surgery in children 9,10,16 . In the majority of these studies, changes in sodium have been trichotomized into either normo‐, hypo‐, or hypernatremia, but as can be seen from Figure , several children crossed more than one boundary within the first 48 h. This led us to explore the various pathways with either decreasing or increasing sodium levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poucos estudos tratam da incidência e evolução das disnatremias em pós-operatório de cirurgia cardíaca. Kaufman et al 49 No presente estudo, a hiponatremia leve foi mais frequente e relacionada a maior tempo de internação em relação à isonatremia. Reconhece-se que a hiponatremia leve está associada a fator de risco independente de mortalidade e não deve ser negligenciada e, portanto, ser tratada prontamente 51,52 .…”
Section: Discussionunclassified
“…Pacientes com hiponatremia tiveram tempo médio mais prolongado de internação (14,1 dias; DP=43,1 versus 5,1 dias; DP=6,1; p<0,000) e de ventilação mecânica (7,3 dias; DP=39,9 versus 1,7 dias; DP=3,5; p<0,000), maior gravidade (PRISM=9,1; DP=7,1 versus 6,6; DP=6,2; p< 0,000) e mortalidade (n=90; 8,5% versus n=24; 3%; p<0,000). ( 12,4) 126 (15,9) 257 (13,9) Procedência; n (%) 0,099* Domiciliar 482 (45,7) 392 (49,6) 874 (47,3) Hospitalar 573 (54,3) 399 (50,4) 972 (52,7) Doenças; n (%) 0,541* Aguda 301 (28,5) 236 (29,8) 537 (29,1) Crônica 754 (71,5) 555 (70,2) 1309 (70,9) Doenças crônicas; n (%) 0,000* Não Complexa 112 (14,9) 124 (22,3) 236 (18,2) Complexa 642 (85,1) 431 (77,7) 1073 (82,2) Diagnóstico Clínico; n (%) Falência Respiratória 211 (35,2) 152 (39,6) 363 (37,0) Sepse / Choque séptico 137 (22,9) 49 (12,8) 186 (18,9) Disfunções Neurológicas 95 (15,9) 81 (21,1) 176 (17,9) ICC / Choque cardiogênico 39 (6,5) 29 (7,6) 68 (6,9) Distúrbio HE-AB 31 …”
Section: Hiponatremia E Isonatremiaunclassified